STRATIFIKASI PENGGUNAAN TAJUK OLEH YAKI (Macaca nigra) DI CAGAR ALAM TANGKOKO DUASUDARA SULAWESI UTARA - Laatung, Sylvia (ZOOTEC, 2015)
THE USE OF SHOOT STRATIFICATION OF YAKI (Macaca nigra) at DUASUDARA TANGKOKO NATURE RESERVE NORTH SULAWESI. The Sulawesi black macaques (Macaca nigra) habitat at the Tangkoko and Duasudara Nature Reserves in North Sulawesi Indonesia has been the focus of periodic assessment since the late 1970s.Â  Ongoing habitat loss and hunting remain the primary threats to the macaques in these adjacent reserves.Â  Surveyed on habitat condition (including vegetation stratum utilization profile) and the interaction between yaki and local people around the nature reserve were conducted over a four-month period. Methods used diagram for habitat profile and interviewed for interaction between yaki and local people. They used stratum A and B frequently (65.21%) in the forest and prefer big trees, with many branch to sleep. The spread of population depends on the availability of resources in the forest. Without increased efforts to reduce hunting pressure and habitat loss, the future of this population is in question. Keywords: The use of shoot stratification, macaca nigra, nature reserve